Transformation of Arabic Assessment in Indonesia: Conventional Assessment Toward Digital Assessment - Nur Fuadi Rahman; Muhammad Ihsanuddin Masdar; Aulia Mustika Ilmiani; Faizal Habibie; Soukaina Samdouni (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
Since 1960, digital assessment has been developed and implemented in foreign language assessments, but there are still few studies that discuss Arabic digital assessment because most of them follow a traditional paper and pencil assessment. The study investigates the transformation of Arabic assessment in Indonesia from conventional to digital. It further describes the factors influencing the transformation. This study employs a qualitative-case study involving Indonesian Islamic State Universities. Data collection techniques used are interviews and observations. Then the data is analyzed interactively with data reduction, data display and conclusion. The results show that the transformation of the Arabic language assessment has begun in 2016 at UIN Maliki Malang but it faced constraints regarding its TOAFL implementation. Implementing the digital Arabic assessment is comprehensively done during the online learning policy. Two factors influence the shift in Arabic assessment culture: the rapid development of the 4.0 Industrial Revolution and the COVID-19 pandemic. There are two models of digital assessment: web-based assessment and mobile-based assessment